Meanings that build Afro-descendant women facing breast and cervical cancer, who were attended in Medellín in Colombia - Ramos-Jaraba, Sara Milena; Carrillo-Pineda, Marcela (Universidad y Salud, 2018)
Introduction: Research on the health of Afro-descendant women is scarce in Colombia, especially when it comes to studies that show the relationship between ethnicity and cancer. Breast cancer and cervix need to be investigated from the voice of Afro-descendant women who suffer from it. Objective: To understand the meanings facing breast or cervix cancer that are built by Afro-descendant women in the health services of Medellín, Colombia. Materials and methods: A qualitative research with an ethnographic approach was made. Semi-structured interviews were conducted for women with breast and cervix cancer and there were focal groups with Afro-descendant population without cancer with observations in medical appointments, chemotherapy and everyday places. The analysis was guided by the Constant Comparative method. Results: Three categories emerged: "Lord Cancer" which accounts for the disease conceived as fatal and dangerous, "the disease displaces", product of the migration of women to Medellin to receive treatments; and "it parts life in two" because of the changes that the disease brings. Conclusion: The disease was conceived beyond the biological part by experiencing an alteration of social, familiar and emotional life. There is a need for greater visibility of the health-disease process of the afro-descendants, or their ancestral role as caregivers and family unit builders.